2015
DOI: 10.1007/s40264-015-0280-1
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Limitations in Observational Studies of the Association Between Glucose-Lowering Medications and All-Cause Mortality: A Review

Abstract: A growing body of observational literature on the association between glucose-lowering treatments and all-cause mortality has been accumulating in recent years. However, many investigations present designs or analyses that inadequately address the methodological challenges involved. We conducted a systematic search with a non-systematic extension to identify observational studies published between 2000 and 2012 that evaluated the effects of glucose-lowering medications on all-cause mortality. We reviewed these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 121 publications
1
51
0
Order By: Relevance
“…An incident user design, which includes patients initiating a treatment of interest or comparator agents, avoids the problem of studying prevalent users who are “survivors” of early adverse effects, allows the evaluation of drug effects that vary over time, and ensures that baseline covariates are assessed before treatment initiation and are not affected by treatment itself . These choices resulted in fair balance in EHR‐based covariates even before PS‐matching, as a testament to the major role played by a proper study design for the achievement of overall study validity . Once adequate study design choices have been made, our findings also suggest that the inclusion of a large number of patient characteristics in the estimation of the PS can further lead to balance of unmeasured but correlated variables by proxy, and as a result, mitigate confounding by the same unmeasured covariates, as previously observed .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…An incident user design, which includes patients initiating a treatment of interest or comparator agents, avoids the problem of studying prevalent users who are “survivors” of early adverse effects, allows the evaluation of drug effects that vary over time, and ensures that baseline covariates are assessed before treatment initiation and are not affected by treatment itself . These choices resulted in fair balance in EHR‐based covariates even before PS‐matching, as a testament to the major role played by a proper study design for the achievement of overall study validity . Once adequate study design choices have been made, our findings also suggest that the inclusion of a large number of patient characteristics in the estimation of the PS can further lead to balance of unmeasured but correlated variables by proxy, and as a result, mitigate confounding by the same unmeasured covariates, as previously observed .…”
Section: Discussionmentioning
confidence: 74%
“…It is often assumed that the absence of this information in pharmacoepidemiological studies could be largely addressed by the application of state‐of‐the‐art study design and analytical choices. For example, in the context of safety and effectiveness research on diabetes therapy, using a new‐user study design enhanced by the proper choice of an active comparator drug, which tends to be used by patients at a similar stage of diabetes, could better distinguish drug effects from diabetes disease effects . Additionally, adjusting analyses via propensity score (PS) matching could leverage the vast information recorded in large claims databases to estimate treatment effects in a population with clinical equipoise regarding many aspects of care, including characteristics that may act as proxies for unmeasured information .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted cumulative exposure modeling proved to be useful as a companion analysis tool. The standard model suggested that timing of past NSAID exposure mattered and WCE models emphasize a key epidemiological concept: Risk should be assessed over a time window that is etiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, metformin has been considered as first‐line therapy in this patient population, similarly to other populations with type 2 diabetes . Nonetheless, observational studies related to the safety and effectiveness of metformin have faced a number of important methodological challenges, including how best to model time‐varying drug exposure because treatment with metformin varies considerably both between patients and within‐patients over time . Metformin use has typically been modeled using a range of time‐fixed measures (ever‐use or total days of use), which do not fully account for the time‐varying nature of the treatment regimens and also largely misclassify exposed person‐time.…”
Section: Introductionmentioning
confidence: 99%